Strike and Fielding Games on Fundamental Movement Skills - Vicki Ahmad Karisman; Gita Febria Friskawati (JUARA : Jurnal Olahraga, 2020)
To be skillful in every sport performance, every child is urged to possess the fundamental motor skills. This study aims to explore the contribution and the use of striking and fielding games in elementary school in an attempt of improving students fundamental motor skills. The researcher utilized an experimental method with pretest and posttest group design. This study invited 34 students of 4th grader as the research sample which was selected by implementing total sampling technique. The treatment was given for 16 meetings. For the instruments, the researcher used the 2nd edition of Test Gross Motor Development (TGMD); which was divided into two kinds of test; those are locomotor and object skill test. Based on the data analysis by using paired sample test, it showed that the significant score of pretest and posttest 0.000 < 0.05. It means that there was a significant improvement of the students’ fundamental motor skills that are intervened by striking and fielding games. This study also indicated that through these games, the students experienced the advancement in their fundamental motor skills. By this advancement, the students are expected to be able to participate actively in their physical activities. In conclusion, this study revealed the significant improvement of the striking and fielding games on the students’ fundamental motor skills.